Aeolothrips eremicola (Thysanoptera, Aeolothripidae): first record of the male from Iran - Alavi, Jalil; Fekrat, Lida; Awal, Mehdi Modarres; Zolfaghari, Maryam; Minaei, Kambiz (Zootaxa, 2013)
The genus Aeolothrips, with 17 recorded species, is the third most species-rich genus in Iran (Minaei 2013). In contrast, the genus Thrips includes 28 species in this country (Minaei 2012; Mirab-balou et al. 2012), and Haplothrips 24 species (Minaei & Aleosfoor 2013), Moreover, it seems likely that more species of Aeolothrips will be discovered in Iran, considering the number recorded from neighboring countries.